Optimization of caprine embryo production in different media for generation of embryonic stem cell-like cells - AGARWAL, SURBHI; KHARCHE, S D; BHATIYA, A K (The Indian Journal of Animal Sciences, 2018)
The aim of the present study was to optimize the production of blastocyst for obtaining caprine embryonic stem cell-like cells. A total of 4372 cumulus oocyte complexes (COCs) were recovered by slicing the 1187 caprine ovaries and were matured in maturation media for 27 h in humidified atmosphere at 38.5°C with 5% CO2 in CO2 incubator. After 27 h of maturation, oocytes were denuded and were co-incubated with buck semen in fertilization medium (TALP medium + 8 mg/ml fatty acid free BSA and 50 μg/ml heparin) for 18 h. Good quality zygotes (2483) were selected and randomly divided into 2 groups (experiment 1), viz. Group 1 (1312) wherein the presumptive zygotes were cultured in RVCL while in Group 2 (1171) the presumptive zygotes were cultured in mCR2aa medium. The cleavage rate, blastocyst and hatched blastocyst production was significantly higher in Gr 1 (47.45±2.93, 10.13±1.31 and 3.90±1.13%) than Gr 2 (37.75±2.46, 4.20±0.93 and 1.66±0.72%). In experiment 2, after in-vitro fertilization, morula stage embryos and inner cell mass (ICM) from blastocyst and hatched blastocyst were used to isolate ES cell-like cells. Thus the results indicated that the RVCL medium is the best medium as far as the embryonic development up to blastocyst stage in comparison to mCR2aa media. Furthermore, the formation of putative embryonic stem cell colonies were higher from hatched blastocysts (91.6%) as compared to that of blastocysts (82.1%) and it was significantly higher than that from morulas (34.3%).